Antioxidant dietary fiber-based bakery products: a new alternative for using plant-by-products - Subiria-Cueto, Carlos Rodrigo; Abraham, Wall-Medrano; Martinez Ruiz, Nina Del Rocio; Rodrigo Garcia, Joaquin; Alvarez-Parrilla, Emilio; Coria-Oliveros, Alma; González Aguilar, Gustavo Adolfo (2021)
Agro-industrial processing activities generate by-products that are discarded at high economic and environmental costs; however, many of them still contain high levels of bioactive compounds (BCs) such as dietary fiber (DF) and phenolic compounds (PCs), which, when combined, are known as antioxidant dietary fiber (ADF). These BCs have properties that are beneficial to our health, among them anti-inflammatory, antioxidant and cardioprotective. Moreover, DF can regulate glucose and cholesterol levels. The mechanism of ADF action depends on its chemical structure and the interactions between the DF and PCs in it. Recent studies have reported the incorporation of several of these by-products on a diet through food products consumed worldwide, such as bread. This review describes the chemical characteristics of the ADF complex and the effect of its molecular interactions on sensory, nutritional and health-promoting properties of functional bakery goods.